Answer:
Then inverse of the given equation is given by ,
(x)= (-x/3 - 6)
Step-by-step explanation:
Given:
Function as g(x)=-3(x+6).
To Find :
The inverse function of the g(x).
Solution:
We know that step involving to convert into inverse function as follows :
Further ,
- Replace g(x) with function as "y",
hence it becomes ,
y=-3(x+6)
2.Then solve for the x value ,
it becomes as ,
=x+6,
-6=x
3. Replace x with y and y with x we get ,
-6=y.
it is written as ,
y=
(x)= -x/3-6
Then inverse of the given equation is given by ,
(x)= -x/3-6.